Hematopoietic stem cell transplantation : a manual for nursing practice - Schmit-Pokorny, Kim; Eisenberg, Seth (Oncology Nursing Society, 2020)
"Hematopoietic stem cell transplantation (HSCT) has evolved from primary use in hematologic malignancies and nonmalignant disease and solid tumors into a treatment option for many other diseases, and indications for HSCT continue to expand. The new edition of this manual provides comprehensive information on the ever-evolving specialty of HSCT, providing nurses and other practitioners with in-depth information on the entire HSCT process, from stem cell mobilization, collection, and infusion to potential complications and long-term effects. It also includes chapters on current research, emerging therapies, ethics, HSCT program development, and professional practice issues"--